Effect of Ag nanoparticles on the radiative properties of tellurite glasses doped with Er3+, Yb3+ and Tm3+ ions - Silva, G. H.; Holgado, D. P. A.; Anjos, V.; Bell, M. J. V.; Kassab, Luciana Reyes Pires [UNESP]; Amancio, Carlos Taveira [UNESP]; Moncorge, Richard (Elsevier B.V., 2014)
The present work is devoted to the characterization of the thermal and spectroscopic properties of tellurite glasses, codoped with Er3+, Yb3+ and Tm3+ rare-earth ions and silver nanoparticles (NPs). The techniques used for this investigation were UV-visible and infrared absorption, time-resolved luminescence and thermal lens. Time-resolved luminescence studies indicate efficient Yb3+ --> Er3+ and Yb3+ --> Tm3+ energy transfers and intense Er3+ and Tm3+ mid-infrared emissions around 1550 nm and 1860 nm, respectively. The presence NPs is found to increase the thermal diffusivity of the materials and to shorten the mid-infrared emission lifetime of both the Er3+ and Tm3+ ions. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Glasses; Metallic nanoparticles; Rare earth ions; Energy transfer; Luminescence; Thermal diffusivity